Governança corporativa como instrumento de solvência nas operadoras de saúde suplementar - Dantas, Liliana Araújo (2020)
Introduction: World historical evolution is accompanied by changes. One of them was the emergence of Good Corporate Governance Practices in order to standardize and optimize processes aiming at the longevity of companies. However, in the healthcare area, many companies have not yet adopted these practices. Objective: To demonstrate the contribution of Corporate Governance and the analysis of indicators in order to increase the solvency of supplementary healthcare operators. Methodology: This is a quantitative and exploratory research based on the triangulation of economic and financial data from 25 supplementary health operators, with more than 100 thousand beneficiaries, which have adopted Corporate Governance. The data were compared with the average of indicators calculated using information from the Financial Statements, available on the website of Agência Nacional de Saúde Suplementar (ANS). Results: The 25 companies analyzed presented indicators above the general average. Conclusion: The application of the principles and pillars of Corporate Governance in the strategies can contribute to the sustainability and financial health of supplementary health operators.